2004
DOI: 10.1109/tcsvt.2004.823396
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Dynamic 3-D Object Shape Reconstruction and High-Fidelity Texture Mapping for 3-D Video

Abstract: Abstract-3D video is a real 3D movie recording the object's full 3D shape, motion, and precise surface texture. This paper first proposes a parallel pipeline processing method for reconstructing dynamic 3D object shape from multi-view video images, by which a temporal series of full 3D voxel representations of the object behavior can be obtained in real-time. To realize the real-time processing, we first introduce a plane-based volume intersection algorithm: represent an observable 3D space by a group of paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 26 publications
0
75
0
Order By: Relevance
“…For higher-quality modeling, especially for reconstructing concave parts, sophisticated model refinement algorithms are required after the shape-from-silhouette, such as deformable mesh (Matsuyama et al, 2004), stereo matching, (Starck & Hilton, 2007;Tomiyama et al, 2004) and graph cuts in the 3D space (Hisatomi et al, 2008;Tung et al, 2008). However, such a model refinement process is out of the scope of this chapter.…”
Section: Flow Of the Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…For higher-quality modeling, especially for reconstructing concave parts, sophisticated model refinement algorithms are required after the shape-from-silhouette, such as deformable mesh (Matsuyama et al, 2004), stereo matching, (Starck & Hilton, 2007;Tomiyama et al, 2004) and graph cuts in the 3D space (Hisatomi et al, 2008;Tung et al, 2008). However, such a model refinement process is out of the scope of this chapter.…”
Section: Flow Of the Algorithmmentioning
confidence: 99%
“…Generation of dynamic three-dimensional (3D) mesh sequences of human performance using multiple cameras has been actively investigated in recent years (de Aguiar et al, 2008;Hisatomi et al, 2008;Kanade et al, 1997;Kim et al, 2007;Matsuyama et al, 2004;Nobuhara & Matsuyama, 2003;Snow et al, 2000;Starck & Hilton, 2007;Tomiyama et al, 2004;Toyoura et al, 2007;Tung et al, 2008;Vlasic et al, 2008). The topic is drawing a lot of attention because conventional 3D shape measurement tools, such as laser scanners, shape (structure)-from-motion (Huang & Netravali, 1994;Poelman & Kanade, 1997), shape-from-shading (Zhang et al, 1999), etc., are difficult to apply to dynamic scenes.…”
Section: Introductionmentioning
confidence: 99%
“…To make full use of the captured video data, we developed a system for generating 3D video [4][9] [10].…”
Section: Generation Of High Fidelity 3d Videomentioning
confidence: 99%
“…We proposed the viewpoint dependent vertex-based texture mapping method to avoid jitters in rendered object images which are caused due to the limited accuracy of the reconstructed 3D object shape [4]. Experimental results showed that the proposed method can generate almost natural looking object images from arbitrary viewpoints.…”
Section: Right Cameramentioning
confidence: 99%
See 1 more Smart Citation